Mebendazole treatment against Anacanthorus penilabiatus (Monogenea, Dactylogyridae) gill parasite of cultivated Piaractus mesopotamicus (Osteichthyes, Characidae) in Brazil. Efficacy and hematology - Martins, Maurício L. [UNESP]; Onaka, Eduardo M. [UNESP]; Moraes, Flávio R. [UNESP]; Fujimoto, Rodrigo Y. [UNESP] (My University, 2001)
The present work evaluated the efficacy of mebendazole (MBZ) treatment against infections with the monogenean helminths Anacanthorus penilabiatus, gill parasites of young cultivated pacu, Piaractus mesopotamicus. A short-term bath treatment using 100, 200 and 500 mg MBZ/1 of water for 10 and 30 min and a long-term bath using 1, 10 and 100 mg MBZ/1 of water for 24 h were utilized. Seven days after, fish were sacrificed and parasites counted. Concentrations of 500 and 200 mg MBZ/1 for 10 and 30 min showed reduced efficacy (0.0 and 0.7%) and (14.2 and 11.0%), respectively. Nevertheless, 100 mg MBZ/1 (10 min) and 10 mg MBZ/1 (24 h) showed better efficacy (79.6 and 81.4%, respectively). Treatments for 24 h provoked increases in hematocrit, hemoglobin concentration and leukocyte number when compared to those untreated fish. Mebendazole treatments also provoked alterations in the defense blood cells especially in lymphocyte and thrombocyte numbers, when the fishes were submitted to 10 and 30 min baths.
Keywords: Anacanthorus penilabiatus; Hematology; Mebendazole; Monogenea; Piaractus mesopotamicus; Treatment; Tropical fish; Characidae; Dactylogyridae; Osteichthyes; Pisces; Vermes